Early neurological deterioration in patients with minor stroke: A single-center study conducted in Vietnam. - Dung Tien Nguyen; Ton Duy Mai; Phuong Viet Dao; Hung Tran Ha; Marco Fabus; Melanie Fleming; Minh Cong Tran (PLoS ONE)
A minor ischemic stroke is associated with a higher likelihood of poor clinical outcomes at 90 days when there is early neurological deterioration (END). The objective of this case-control study conducted in a comprehensive stroke facility in Vietnam is to examine the frequency, forecast, and outcomes of patients with END in minor strokes. The study employs a descriptive observational design, longitudinally tracking patients with minor strokes admitted to Bach Mai Hospital's Stroke Center between December 1, 2023, and August 31, 2024. Hospitalized within 24 hours of symptom onset, minor stroke patients with National Institutes of Health Stroke Scale (NIHSS) scores ≤ 5 and items 1a, 1b, and 1c on the NIHSS scale, each equal to 0, were included in the study. The primary measure of interest is the END rate, defined as a rise of 2 or more points in the NIHSS score during the first 72 hours after admission. We conduct a logistic regression analysis to identify forecasting factors for END. Out of 839 patients, 88 (10.5%) had END. In the END group, we found that most patients had complications within the first 24 hours of stroke, accounting for 43.2%; the 24 - 48-hour window accounted for 35.2%, and the 48 - 72-hour window accounted for 21.6%. END was associated with a higher likelihood of poor outcomes (mRS 2 - 6) at discharge (OR = 22.76; 95% CI 11.22 - 46.20; p < 0.01), 30 days post-stroke(OR = 24.38; 95% CI 14.40 - 41.29; p < 0.01), and 90 days post-stroke (OR = 21.74; 95% CI 12.63 - 37.43; p < 0.01). Some of the prognostic factors for END were admission NIHSS score (OR = 1.24; 95% CI 1.03 - 1.49; p = 0.02), admission systolic blood pressure greater than 150mmHg (OR = 1.70; 95% CI 1.03 - 2.81; p = 0.04), admission blood glucose (OR = 1.07; 95% CI 1.01 - 1.14; p = 0.02), reperfusion therapy (OR = 3.35; 95% CI 1.50 - 7.49; p < 0.01), use of antiplatelet monotherapy (OR = 3.69; 95% CI 2.24 - 6.08; p < 0.01), internal capsule infarction (OR = 2.54; 95% CI 1.37 - 4.71; p < 0.01), hemorrhagic transformation (OR = 5.72; 95% CI 1.07 - 30.45; p = 0.04), corresponding extracranial carotid artery occlusion (OR = 4.84; 95% CI 1.26 - 18.65; p = 0.02), and middle cerebral artery occlusion OR = 3.06; 95% CI 1.29 - 7.30; p = 0.01). END in minor stroke patients accounts for 10.5% and is a risk factor for poor neurological outcomes. Admission NIHSS score, higher systolic blood pressure, admission blood glucose, reperfusion therapy, use of antiplatelet monotherapy, internal capsule infarction, hemorrhagic transformation, corresponding extracranial carotid artery occlusion, and middle cerebral artery occlusion were some of the prognostic factors for END in our observational study.